2006
DOI: 10.1186/1477-7819-4-53
|View full text |Cite
|
Sign up to set email alerts
|

Time-related improvement of survival in resectable gastric cancer: the role of Japanese-style gastrectomy with D2 lymphadenectomy and adjuvant chemotherapy

Abstract: The global prognosis and that of some stages have improved in recent years with case RGC patients treated with surgery and adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Two studies from the Memorial Sloan-Kettering Cancer Center demonstrated survival differences for T1-T3 tumors in favor of Japanese patients and improved survival after matching by T stage and location in Korean patients compared to the US patients (26,27). However, as observed in our recent and previous study, it is promising that the inconsistency of the surgical approach between Japan and the Western groups, particularly in terms of the extent of nodal resection, is being eliminated, such that better outcomes in the D2 groups with an operative mortality rate of less than 4% and an increased rate of cases having at least 15 lymph nodes removed is being reported both in randomized control trials and observational studies by surgical teams who had acquired experience through the years spent in Western countries (11,(28)(29)(30)(31)(32)(33)(34)(35)(36). The results of the Dutch and UK trials have been criticized for the unacceptably high mortality and poor survival rates, as well as the non-compliance of surgeons (24).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from the Memorial Sloan-Kettering Cancer Center demonstrated survival differences for T1-T3 tumors in favor of Japanese patients and improved survival after matching by T stage and location in Korean patients compared to the US patients (26,27). However, as observed in our recent and previous study, it is promising that the inconsistency of the surgical approach between Japan and the Western groups, particularly in terms of the extent of nodal resection, is being eliminated, such that better outcomes in the D2 groups with an operative mortality rate of less than 4% and an increased rate of cases having at least 15 lymph nodes removed is being reported both in randomized control trials and observational studies by surgical teams who had acquired experience through the years spent in Western countries (11,(28)(29)(30)(31)(32)(33)(34)(35)(36). The results of the Dutch and UK trials have been criticized for the unacceptably high mortality and poor survival rates, as well as the non-compliance of surgeons (24).…”
Section: Discussionmentioning
confidence: 99%
“…The overall survival rates of the present study after D2 radical gastrectomy are similar to other studies. 6,21,22 Experience of the surgeon is another important factor for a safe and adequate D2 radical gastrectomy. The high number of removed lymph nodes (Table 1) is a good indicator for the experience and practice of the surgeons who took part in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure was performed according to standards described elsewhere [15][16][17]. Resected specimens were examined according to standard pathohistological procedures and classified according to criteria described by the Japanese Research Society for Gastric Cancer [15][16][17]. The anatomical location, diameter of the tumor, lymphocyte invasion, vascular invasion, lymphangial invasion, extranodal invasion, and perineural invasion were all noted.…”
Section: Surgery and Pathohistological Tumor Classificationmentioning
confidence: 99%
“…The strategy was to achieve R0 resection (assuring 4-5-cm tumor-free safety margins in intestinal type; 8-10-cm tumor-free safety margins in diffuse type according to Lauren) accompanied by D2 lymphadenectomy. The surgical procedure was performed according to standards described elsewhere [15][16][17]. Resected specimens were examined according to standard pathohistological procedures and classified according to criteria described by the Japanese Research Society for Gastric Cancer [15][16][17].…”
Section: Surgery and Pathohistological Tumor Classificationmentioning
confidence: 99%